PENGEMBANGAN PERANGKAT AJAR MODEL CORE PENDEKATAN METAKOGNITIF UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH GEOMETRI KELAS VIII - Sa’adah, Daroinis; Masrukan, Masrukan; Kuniasih, Ary Woro (JURNAL e-DuMath, 2017)
The objectives of this study are to develop teaching aids, to test the validity and practically teaching aids, and to test the effectiveness of learning process using CORE (Connecting, Organizing, Reflecting, and Extending) model with metacognitive approach to improve the ability in Geometri problem solving. This research and development design is adapted from Plomp model by using several phases: (1) preliminary investigation; (2) design; (3) realization/construction; (4) test, evaluation and revision. This study developed some teaching aids; a part of syllabus, lesson plan, students book, studentsâ work sheet, and test of problem solving ability. The subject of the try out is eighth graders of MTs NU Nurul Huda Kudus. The research data to test the validity, practically, and effectiveness are collected by: (1) validation sheet; (2) observation sheet; (3) problem solving test. The results of research showed that development teaching aids using CORE model with metacognitive approach for Geometry material of VIII grade is valid and practical, and learning CORE model with metacognitive approach for Geometry material of VIII grade is effective.